Laba Dan Profitabilitas - Elfreda Aplonia Lau (Prodi Ilmu Administrasi Negara, 2016)
The profit is the dream of every profit-oriented company. It can be expressed in various levels of understanding. Classification of profitcan be observed from several aspects. One among others that the profits seen from the financial report, it is divided into the gross profit,profit before interest and tax (EBIT), profit before tax and profit after tax or net profit. Each of these benefit terms are meaningful for stakeholders and shareholders. Profits can be used for reflectingprofitability, it depends on the intended profitability indicators.Profitability of a company will affect the policy of the investors on the investment made. The company's ability to generate profits will be able to attract investors to invest their funds in order to expand its business, otherwise the low level of profitability that will cause investors to withdraw their funds. Value of profitability can be the norm for the health of the company. Profitability is the company's ability to generate profits or profit that will be the basis of dividen. Profitability describes the ability of businesses to generate profits using all capital owned.Any gains may be a reflection of profitability. However, it should be distinguished by profitability indicators to be addressed, due to it can be measured by various criteria (Gross profit margin, Operating income ratio/Operating profit margin, Net profit margin/sales margin, Earning power of total investment/Rate of return on total assets, Net earnings power ratio/rate of return on investment and Net earning power ratio/rate of return on investment).Profitability is very meaningful to management at various levels in the workplace as well as evaluating the performance of each unit as well as a unified company/organization. Value of profitability is significant for investors, meaningful for the community, significant for banks, meaningful for the government, meaningful for employees mainly in their contribution to the company or organization they work.